Structural e-permits: an openBIM, model-based procedure for permit applications pertaining to structural engineering - Ciotta, Vittoria; Ciccone, Angelo; Asprone, Domenico; Manfredi, Gaetano; Cosenza, Edoardo (Journal of Civil Engineering and Management, 2021)
This paper investigates the creation and use of integrated IFC models to modernise traditional processes for applications to building authorities for structural engineering approvals and permits. First, we provide a brief overview of e-permit systems in the AEC sector, with the focus on solutions that implement openBIM standards like IFC, MVD, and IDM. Second, we conduct a study on the information requirements of Italy’s seismic-authorisation processes relating specifically to the field of structural engineering. Third, we describe preliminary research on defining the structural engineering information that needs to be incorporated in the IFC format for e-permitting scopes. Fourth, we present our early work on the development of an MVD that would enable the automatic extraction of integrated IFC models. Fifth, we illustrate the reference workflow of the Str.E.Pe. project and propose a preliminary proof-of-concept that makes use of an IFC model, which has been integrated with structural information to support the activities of the building authority in Avellino. The officers there have developed a SWOT analysis using IFC models to assist them in assessing the compliance of structural projects with seismic requirements. Finally, the paper sets out additional research we intend to undertake and our conclusions.